Advice on assistance and protection provided by the Scientific Advisory Board of the Organisation for the Prohibition of Chemical Weapons: Part 1. On medical care and treatment of injuries from nerve agents. (1st March 2019) - Timperley, Christopher M.; Forman, Jonathan E.; Abdollahi, Mohammad; Al-Amri, Abdullah Saeed; Baulig, Augustin; Benachour, Djafer; Borrett, Veronica; Cariño, Flerida A.; Geist, Michael; Gonzalez, David; Kane, William; Kovarik, Zrinka; et al.
Graphical abstract: Highlights: Work of the Organisation of the Prohibition of Chemical Weapons (OPCW) is described. Advice on assistance and protection from OPCW Scientific Advisory Board is presented. The advice addresses medical care/treatment of injuries from nerve agents. Scientific literature on the topics is reviewed and over 140 references highlighted. This advice serves as a resource for toxicologists, medics and emergency responders. Abstract: The Scientific Advisory Board (SAB) of the Organisation for the Prohibition of Chemical Weapons (OPCW) has provided advice on assistance and protection in relation to the Chemical Weapons Convention. In this, the first of several papers describing the SAB's work on this topic, we describe advice given in response to questions from the OPCW Director-General in 2013 and 2014 on the status of available medical countermeasures and treatments to organophosphorus nerve agents. This paper provides the evidence base for this advice which recommended to the OPCW pretreatments, emergency care, and long-term treatments that were available at the time of the request for this class of chemical warfare agent (CWA). It includes a bibliography of over 140 scientific references, which can be used as a platform for watching future medical countermeasure developments. The information provided in this paper should serve as a valuable reference for medical professionals and emergency responders who may have no knowledge of the symptoms and treatment options of exposure to nerve agents.